Effect of extract from common oat on the antioxidant activity and fatty acid composition of the muscular tissues of geese - O. O. Danchenko; Y. V. Nicolaeva; O. I. Koshelev; M. M. Danchenko; O. V. Yakoviichuk; T. I. Halko (Regulatory Mechanisms in Biosystems, 2021)
Among natural antioxidants, increasing attention is being drawn to avenanthramides - phenolic compounds of the common oat Avena sativa (Linnaeus, 1753). Research has shown that avenanthramides have much higher antioxidant activity than well-known bioflavanoids. Currently, a great deal of work is being conducted on the structure of these compounds and mechanisms of their effect on the organism of humans and animals. We explored the specifics of the influence of aqueous extract from A. satíva on the antioxidant activity and fatty acid composition of lipids of histologically similar tissues of geese with different levels of aerobicity (muscles of the stomach and cardiac muscle), dynamics of the birds’ live weight and pterylographic parameters under physiological loading by the development of contour and juvenile feathers. The addition of extract of oat to the diet of geese during growth of feathers was observed to increase the antioxidant activity of their tissues. Physiological loading related to the development of contour feathers in the examined tissues of geese significantly weakens as a result of selective inhibition of synthesis of unsaturated fatty acids, especially oleic acid, the content of which in 28-day old geese of the experimental group decreased by 31.7 in the cardiac muscle and 46.8 times in the stomach, compared with the control. Further changes in fatty acid composition were characterized by lower number of differences between the control and experimental groups. Increase in antioxidant activity in these tissues during development of juvenile feathers (day 49) occurs as a result of activation of alternative mechanisms of antioxidative protection, which take place with no significant changes in fatty acid composition. Furthermore, we determined that in the stomach and cardiac muscles of geese, the action of extract from common oat activated mechanisms of antioxidative protection, which increased the level of correlation between the changes in fatty acid composition. The study confirmed that the extract caused not only significant increase in the weight of geese at the end of the experiment, but also improved their pterylographic parameters. Therefore, it is practical to conduct similar studies on wild species of birds grown for hunting, because this process of development of feathers, particularly for such species of birds, is essential.